Patient-Derived Induced Pluripotent Stem Cells (iPSCs) and Cerebral Organoids for Drug Screening and Development in Autism Spectrum Disorder: Opportunities and Challenges - Chiara Villa; Romina Combi; Donatella Conconi; Marialuisa Lavitrano (MDPI AG, 2021)
Autism spectrum disorder (ASD) represents a group of neurodevelopmental diseases characterized by persistent deficits in social communication, interaction, and repetitive patterns of behaviors, interests, and activities. The etiopathogenesis is multifactorial with complex interactions between genetic and environmental factors. The clinical heterogeneity and complex etiology of this pediatric disorder have limited the development of pharmacological therapies. The major limit to ASD research remains a lack of relevant human disease models which can faithfully recapitulate key features of the human pathology and represent its genetic heterogeneity. Recent advances in induced pluripotent stem cells (iPSCs), reprogrammed from somatic cells of patients into all types of patient-specific neural cells, have provided a promising cellular tool for disease modeling and development of novel drug treatments. The iPSCs technology allowed not only a better investigation of the disease etiopathogenesis but also opened up the potential for personalized therapies and offered new opportunities for drug discovery, pharmacological screening, and toxicity assessment. Moreover, iPSCs can be differentiated and organized into three-dimensional (3D) organoids, providing a model which mimics the complexity of the brain's architecture and more accurately recapitulates tissue- and organ-level disease pathophysiology. The aims of this review were to describe the current state of the art of the use of human patient-derived iPSCs and brain organoids in modeling ASD and developing novel therapeutic strategies and to discuss the opportunities and major challenges in this rapidly moving field.